2010
DOI: 10.1177/1078155210382318
|View full text |Cite
|
Sign up to set email alerts
|

Transfusions increase with nationally driven reimbursement changes of erythropoiesis stimulating agents for chemotherapy-induced anemia

Abstract: The primary goal of reducing the number of transfusions in patients with CIA by administering ESAs cannot be met when clinical practice coincides with the NCD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 13 publications
(15 reference statements)
0
10
0
Order By: Relevance
“…At the time we performed our study, published studies describing the NCD impact on patient care suggested an increase in transfusions among chemotherapy‐treated cancer patients; however, these studies involved single centers or regional groups of clinics. A more recently published study involves oncology centers from around the country, but is not necessarily nationally representative .…”
Section: Introductionmentioning
confidence: 99%
“…At the time we performed our study, published studies describing the NCD impact on patient care suggested an increase in transfusions among chemotherapy‐treated cancer patients; however, these studies involved single centers or regional groups of clinics. A more recently published study involves oncology centers from around the country, but is not necessarily nationally representative .…”
Section: Introductionmentioning
confidence: 99%
“…Several studies reported increases in RBC transfusion rates after NCD 8‐11,15,16 while others reported no impact 7,12,14 . Our post hoc analysis comparing transfusion trends among all Medicare FFS beneficiaries suggests that a secular trend unrelated to ESA use, NCD, REMS implementation, or REMS discontinuation was responsible for the observed small changes in transfusion (eFigure S9).…”
Section: Discussionmentioning
confidence: 77%
“…Prior studies demonstrated that ESA administration to patients with cancer dropped substantially following NCD 7‐15 . Six of nine studies assessing the impact of NCD on red blood cell (RBC) transfusions reported increased transfusion rates 8‐11,15,16 ; three showed no significant changes 7,12,14 . Four studies assessing the impact of the REMS reported decreased use of ESAs after REMS approval and inconsistent RBC transfusion results 9,15,17,18 …”
Section: Introductionmentioning
confidence: 99%
“…Some previous studies have examined the change in the use of ESAs and blood transfusions in cancer patients before and after the implementation of the Medicare reimbursement policy change. [32][33][34][35][36][37] Documented in the literature is a 26%-57% reduction in the use of ESAs after the policy change. [32][33][34][35] Results are mixed regarding the change in the use of blood transfusions.…”
Section: What This Study Addsmentioning
confidence: 99%